OSHA AND SECONDHAND SMOKE (Tufts Archival Research Center, 2007)
Proposal prepared by Powell Tate in response to Occupational Safety and Health Administration's (OSHA) proposed regulations regarding secondhand smoke. Expresses concern at the potential implication of OSHA's proposal to ban smoking in the majority of workplaces. Recommends a two phase campaign to be implemented by the Tobacco Industry's Labor Management Committee in demonstrating that OSHA's ban is unreasonable. Focuses on the need to get OSHA to regulate IAQ without banning smoking altogether. Describes the synthesis of spokespeople, decision-makers, created materials, the media and congressional influence in achieving the tobacco industry's goals. Emphasizes that labor will play an important role in affecting this policy.